KOMPARASI KEWENANGAN PRAPERADILAN ANTARA INDONESIA DENGAN ITALIA: Comparison Of Pretrial Authority Between Indonesia And Italy - Dewi Natasya Lestari; Setiyono (Reformasi Hukum Trisakti, 2025)
Pretrial is a legal mechanism that serves as a means of control over the actions of law enforcement officials, especially in the process of investigation and detention. In Indonesia, pretrial authority is regulated in the Criminal Procedure Code (KUHAP) and Constitutional Court Decision No. 21/PUU-XII/2014, which focuses on procedural testing, such as the legality of arrest, detention, confiscation, termination of investigation, termination of prosecution, and determination of suspects. On the other hand, Italian pretrial is regulated in the Codice di Procedura Penale, which grants broader authority to the Giudice per le Indagini Preliminari to oversee both of the procedural aspects and the substance of investigations and prosecutions. The results show that the Italian pretrial institution provides relatively responsive protection to the human rights of suspects or defendants, because structurally the investigative judge has the authority to examine procedural aspects from the beginning of the investigation. Indonesia's pretrial institutions have relatively limited authority to examine the formal procedural aspects of actions taken by investigators and public prosecutors. This comparison suggests that there is an opportunity for Indonesia to improve pretrial effectiveness by adopting the checks and balances principles applied in Italy.